Transformational leadership style and its relationship with change management - Aymn Sulieman Alqatawenah (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
Transformational leadership is considered one of the main leadership styles that influence organizational and individual outcomes to achieve competitive advantage. This study aims to identify the relationship between some dimensions of transformational leadership namely: Idealized Influence, Inspirational motivation, Intellectual stimulation and empowerment, and change management in Jordanian Insurance companies. A questionnaire was developed to investigate the dimensions of the study and was applied to a sample that consisted of 500 respondents. SPSS package was utilized to analyze the quantitative data. The study has concluded that the dimensions of the transformational leadership (Idealized Influence, Inspirational motivation, Intellectual stimulation and Empowerment) and change management are available in Jordanian Insurance companies. The study contributes by recommending organizations to conduct and organize training courses to enhance the capability of the workers by promoting empowerment's behaviors, also taking into account the individual differences between the employees, particularly in assigning work and tasks.
Keywords: L22; 650; transformational leadership; change management; insurance companies; Jordan